Osprey optimization algorithm for distributed generation integration in a radial distribution system for power loss reduction - P. Rajakumar; P. M. Balasubramaniam; Arunkumar Munimathan; Mamdooh Alwetaishi; Mohammad Imtiyaz Gulbarga; Chinnaiyan Senthilpari (Scientific Reports)
Abstract Many optimization algorithms were proposed in the past and optimized the distributed generation (DG) in the radial power distribution networks. However, most of the algorithms suffer from poor convergence and local optima stagnation issues due to the complicatedness of the problem. Several new algorithms and enhanced algorithms are recently developed to resolve numerous engineering problems. In this study, an optimization method is developed using the Osprey optimization algorithm (OOA) to determine the best possible solution for the complex DG placement problem. The proposed OOA method optimizes the appropriate size and location for a Type I and III DG to reduce the RDS’s real power losses (RPL). The adequacy of the proposed technique is investigated on the IEEE 33-bus and 118-bus radial PDNs. Furthermore, a real-time Malaysian 54-bus radial PDN is considered to verify the adaptability of the proposed approach. The proposed technique optimized DG placement has minimized the RPL in the IEEE 33-bus radial PDN by 52.47% (Type-I) and 71.95% (Type-III) and likewise, in the Malaysian 54-bus radial PDN the power losses are cut down by 72.56% (Type-I) and 94.88% (Type-III). Moreover, the proposed OOA technique provided better results than the popular and recent optimization techniques cited in literature.